Inter-budget relations in contemporary Kazakhstan - Issakhova, A. S. (Journal of Economic Research & Business Administration, 2015)
The demise of the Soviet Union has effected a significant shift in Kazakhstani budgetary system from a highly centralized “colonial” government to an independent self-governing state. Currently, Kazakhstan faces the problem of concentration of budgetary decision-making power at the governmental center, but the general economic and political trend for increased regional budgetary independence is evident. This article traces the characteristics of the financial and economic behavior of government, namely, discusses the role of intergovernmental relations in the country’s budgetary system and budgetary problems of asymmetry. A fairly high share of transfers - budgetary and subvention removals – is shown. The analysis of key statistical indicators regions.The mechanisms and instruments of inter-budgetary alignment, directed to strengthen the financial base of local budgets, are revealed.